Prevalence of obesity and its associated risk factors among the elderly in Malaysia: Findings from The National Health and Morbidity Survey (NHMS) 2015 - Ariaratnam, Suthahar; Rodzlan Hasani, Wan Shakira; Krishnapillai, Ambigga Devi; Abd Hamid, Hamizatul Akmal; Shariff Ghazali, Sazlina; Mohd Tohit, Noorlaili (Public Library of Science (PLoS), 2020)
Background: Obesity is a crucial public health problem and is rising globally. This study was conducted to determine the prevalence of obesity and its associated factors among the elderly in Malaysia. Methods: Data were obtained from the National Health and Morbidity Survey (NHMS) 2015. This was a cross sectional population-based study using a two stage stratified random sampling design. Elderly population aged 60 years and above was selected. Data were collected using pre-tested self-administered questionnaire in the form of sociodemographic profile, non-communicable diseases (NCD) comorbidities (status on hypertension, diabetes and hypercholesterolemia) and NCD risk factors (current smoker and physical activity). Obesity has been defined using the World Health Organization (WHO) Body Mass Index (BMI) guideline, 1998. A complex sampling design analysis was used for the descriptive statistics. The associated risk factors for obesity were identified using Multiple Logistic Regression analysis. Results: A total of 3794 respondents were included in this study. The prevalence of obesity among Malaysian elderly was 30.2%. The prevalence of obesity among the elderly was significantly higher in females, respondents from urban areas and Indians. Approximately one third of the elderly with non-communicable diseases such as hypertension (33.1%) and diabetes (38.8%), respectively, were obese. Among elderly who were obese, majority of them (89.8%) had at least one NCD. The prevalence of obesity was 16.8% among current smokers (aOR 0.59). Multiple logistic regression analysis revealed that elderly females (aOR [adjusted odds ratio] 1.52), having secondary education (aOR 1.96) with household income of RM 3000 and above (aOR 1.57) as well as being hypertensive (aOR 1.61) and diabetic (aOR 1.50) were more likely to be obese. In contrast, the Chinese elderly respondents (aOR 0.62) and current smokers (aOR 0.59) were less likely to be obese. There were no significant associations of obesity with hypercholesterolemia or with physical activity. Conclusions: A substantial proportion of Malaysian elderly were obese, and factors associated with obesity among them were being female, having secondary education with a household income of RM 3000 and above and being hypertensive or diabetic. Enhanced health promotion and education should be targeted at younger people in order to prevent obesity in the later years.